Pengaruh Perilaku Pengguna Pada Keputusan Pembelian Item Virtual Game Roblox Di Itemku.Com - Zikri Alif; Yentisna (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to analyze the Influence of User Behavior on the Purchasing Decision of Virtual Items in Roblox at Itemku.Com. This study employs a quantitative method with data collection through questionnaires distributed to 96 student respondents using purposive sampling techniques. Based on the research results and data analysis using SPSS (Statistical Product and Service Solutions) indicates that: (1) Price Utility has a positive and significant effect on purchasing decisions, (2) Functional Quality has a positive and significant effect on purchasing decisions, (3) Trust has a positive and significant effect on purchasing decisions, (4) Customer Satisfaction has an effect on purchasing decisions, (5) Happiness has a positive and significant effect on purchasing decisions, (6) Price Utility, Functional Quality, Trust, Customer Satisfaction, and Happiness have a positive influence on and significantly affects Purchase Decisions. Simultaneously, all five independent variables have a significant effect on purchasing decisions. These findings indicate that Roblox games on Itemku.com play a role in shaping consumer preferences for purchases in the city of Padang.